In the name of God : the Bible in the colonial discourse of empire - Crouch, Carly L. 1982-; Stökl, Jonathan, 1977- (Biblical Interpretation Series, 2013)
In In the Name of God biblical scholars and historians begin the exciting work of deconstructing British and Spanish imperial usage of the Bible as well as the use of the Bible to counteract imperialism. Six essays explore the intersections of political movements and biblical exegesis. Individual contributions examine English political theorists' use of the Bible in the context of secularisation, analyse the theological discussion of discoveries in the New World in a context of fraught Jewish-Christian relations in Europe and dissect millennarian preaching in the lead up to the Crimean War. Others investigate the anti-imperialist use of the Bible in southern Africa, compare Spanish and British biblicisation techniques and trace the effects of biblically-rooted articulations of nationalism on the development of Hinduism's relationship to the Vedas. Contributors include: Yvonne Sherwood, Ana Valdez, Mark Somos, Andrew Mein, Hendrik Bosman and Hugh Pyper.